Mangrove and Gastropoda Community Structure in The Coastal of Kampung Laut, Cilacap District - Rahman, Abdul -; Pasaribu, Roberto Patar; Pattirane, Chrisoetanto P.; Djari, Anthon Anthonny; Hidayah, Dwi Nur (Politeknik Ahli Usaha Perikanan, 2024)
Mangrove forest is a type of forest found in tidal areas which are inundated at high tide and dry at low tide. Gastropods are biota that are closely related to mangrove ecosystems and are found in many environmental conditions. The purpose of this study was to determine the community structure between mangroves and gastropods associated with mangrove forest areas in Kampung Laut Coast, Cilacap Regency. The results obtained for the most mangrove species were Rhizophora apiculata and Brugeria. Mangrove canopy cover value of 75.56% is included in the good category with dense density. There were 6 types of gastropods associated with mangroves, namely Caenogastropoda, Cycloneritida, Ellobiidae, Neritidae, Potamididae, and Muricidae. The relationship between mangrove ecosystems and gastropods in the Kampung Laut coast is very close. This is due to the fact that most of this area is overgrown with mangrove species Rhizopora spp which are very popular with gastropods.